2009
DOI: 10.1016/j.dsr.2009.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Thorium-234 as a tracer of spatial, temporal and vertical variability in particle flux in the North Pacific

Abstract: An extensive 234 Th data set was collected at two sites in the North Pacific: ALOHA, an oligotrophic site near Hawaii, and K2, a mesotrophic HNLC site in the NW Pacific as part of the VERTIGO (VERtical Transport in the Global Ocean) study. Total 234 Th:238 U activity ratios near 1.0 indicated low particle fluxes at ALOHA, while 234 Th: 238 U ~0.6 in the euphotic zone at K2 indicated higher particle export. However, spatial variability was large at both sites-even greater than seasonal variability as reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 95 publications
3
47
0
2
Order By: Relevance
“…Currents in the region vary with both depth and season, (Hickey, 1991(Hickey, , 1992 and likely cause spatial separation between the locations where particles are generated and where they settle. Particle flux variability across space (Buesseler et al, 2009) may interact with these seasonal currents, resulting in seasonally variable particle delivery to the sea floor at SPOT. Water below the sill of the San Pedro basin at 750 m is primarily trapped (Berelson, 1991), suggesting that currents alone seem like an unlikely explanation for the greater seasonality at 890 m than at intermediate depths.…”
Section: Discussionmentioning
confidence: 99%
“…Currents in the region vary with both depth and season, (Hickey, 1991(Hickey, , 1992 and likely cause spatial separation between the locations where particles are generated and where they settle. Particle flux variability across space (Buesseler et al, 2009) may interact with these seasonal currents, resulting in seasonally variable particle delivery to the sea floor at SPOT. Water below the sill of the San Pedro basin at 750 m is primarily trapped (Berelson, 1991), suggesting that currents alone seem like an unlikely explanation for the greater seasonality at 890 m than at intermediate depths.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, smaller volume methods that require as little as 1 L, but typically 4 L , were developed and have since been applied widely (Buesseler et al, 2008a;Buesseler et al, 2008b;Cai et al, 2008;Martin et al, 2011). This method requires knowledge of the 238 U activity in seawater.…”
Section: Methods Of Measuring Particle Exportmentioning
confidence: 99%
“…As export flux is a product of complex interactions between mixing, phytoplankton, and zooplankton, it is likely that the scales of variability of export are of a 19 similar scale to phytoplankton or smaller. Results from studies using 234 Th and underwater cameras have hinted at this smaller scale variability of export (Guidi et al, 2007;Buesseler et al, 2008b; Guidi et al, 2008). A recent study modeling export flux and measurements of 234 Th has demonstrated the heterogeneity of export on scales of 100 km and less .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous processes can impact POC/ 234 Th ratios in the ocean including particle surface-area-to-volume ratios , solution chemistry issues (Guo et al, 2002;Hung et al, 2004), the chemical composition of particles and their affinity for 234 Th (Szlosek et al, 2009), POC assimilation by food webs (Buesseler and Boyd, 2009), particle aggregation (Burd et al, 2000) and fragmentation (Maiti et al, 2010) and Th decay (Cai et al, 2006). …”
Section: Determination Of Poc : 234 Th Ratio Of Sinking Particlesmentioning
confidence: 99%